Case Report: Hepatic Sarcoid-Like Reaction Associated With Checkpoint Inhibition in a NSCLC Patient and a Literature Review - Lin, Yuxin; Zhu, Wei; Wu, Bingchen; Lan, Huiyin (Frontiers in Oncology, 2022)
Immune checkpoint inhibitor (ICI) treatment has dramatically revolutionized the landscape of therapeutic approaches in multiple cancers, including non-small-cell lung cancer (NSCLC). With the increasing use of programmed death-1 (PD-1) inhibitors in the clinic, the emerging toxicity profile presents a novel learning curve for clinicians. Here we report the first case of a NSCLC patient displaying sarcoid/granulomatous-like reaction (SLR, also known as GLR) in liver during anti-PD-1 therapy which showed efficacious response of complete regression. Also, this is the first report describing the SLR induced by toripalimab, a novel PD-1 inhibitor. Given this kind of hepatic findings can be easily mistaken as metastasis, even resulting in premature use of second-line treatments, in particular, we briefly review the clinical features of all those cases reporting sarcoidosis and SLRs manifested on different organs during anti-PD-(L)1 therapy. We anticipate that these clinical cases would help to alert clinicians’ attention that SLRs, as a rare immune-related adverse event (irAE), is manageable and histopathological analyses is necessary before interpreting it as disease progression.